Oracle database workload performance measurement and tuning toolkit - Lee, S.P.; Zildzic, D. (2006)
Database tuning practice is mainly conducted as a consequence of user's complaints on the performance. There is a need for a reactive monitoring and tuning tool enabling a real-time overview of the main resource consumers in order to detect and solve performance bottlenecks. With an assessment of the Oracle's high-availability database, in terms of the main architectural components and their impact on performance, we have developed a Java tool for the efficient and resource- effective tuning of Oracle databases. Our tool, called Workload Performance Monitoring and Tuning (WPMT), enables proactive and reactive database tuning. By combining today's best monitoring and tuning practices with our metrics management, we have designed a unique approach to illustrate the efficiency of the Oracle database memory segments responsible for handling the workload. This approach consists of developing database memory delta charts, illustrating the efficiency of memory initialization parameters versus component's workload performance.